Cambodia Economic Update, November 2020 : Restrained Recovery - World Bank (World Bank, Phnom Penh, 2020)
The Coronavirus disease (COVID-19) pandemic has abruptly interrupted Cambodia’s celebrated growth story. The pandemic has effectively stalled the construction and real estate boom that relied heavily on foreign investment. High-frequency phone surveys of households validated the adverse impact of the pandemic on employment. As the global economic crisis caused by COVID-19 continues, the economy in 2020 is projected to contract by 2.0 percent, the sharpest decline in Cambodia’s recent history. The most important policy goal must be to urgently regain jobs lost or suspended due to the pandemic. In this regard, full attention must be paid to boost investment in labor-intensive sectors to generate jobs. Looking ahead, it is essential to facilitate an expansion of domestic and foreign investment arising largely from recent bilateral and regional free trade agreements. It is imperative to continue to closely monitor vulnerabilities arising from a prolonged construction and property boom and the increase of credit provided to the construction and real estate sector. It is critically important to develop a COVID-19 vaccine distribution infrastructure, while identifying potential COVID-19 vaccine availability and affordability. Cooperation has been sought with regional countries developing COVID-19 vaccines such as China to ensure Cambodia has access to the COVID-19 vaccine when it is available.